The control charts with curtailment - Ng, David Hong Sheng. (2012)
The optimization design of a control chart had been an area of great research interest since the availability of computing resources. Through the use of computer simulations, solutions can be found for this complex problem. However, the optimization of a control chart can be solved through the application of many different objective functions, and as a result, there lies a myriad of solutions.